2019
DOI: 10.1155/2019/8345309
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Related Osteonecrosis of the Jaws: Two Center Retrospective Cohort Studies

Abstract: This retrospective cohort study aims to describe characteristics of patients with MRONJ, to identify factors associated with MRONJ development, and to examine variables associated with favourable outcome. Totally 32 patients were followed and observed: 21 females and 11 males, in the age range 35-84 in the period from 2009 to 2018. Clinical, radiological examination (Orthopantomograph and CBCT) and biopsy were performed in order to achieve diagnosis. Demographic and clinical variables were taken into considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…27,28 Early surgical treatment may prevent progression of the lesions, reduce risk of postoperative recurrence, and improve prognosis. [28][29][30] In this study, we found preoperative MRONJ duration $12 months to be associated with advanced MRONJ stage; this finding supports the view of early surgical treatment for MRONJ.…”
Section: Discussionsupporting
confidence: 83%
“…27,28 Early surgical treatment may prevent progression of the lesions, reduce risk of postoperative recurrence, and improve prognosis. [28][29][30] In this study, we found preoperative MRONJ duration $12 months to be associated with advanced MRONJ stage; this finding supports the view of early surgical treatment for MRONJ.…”
Section: Discussionsupporting
confidence: 83%
“…The importance of tooth extraction in enhancing a pro-inflammatory environment in the tooth extraction socket was verified by comparing the operated- and non-operated side of the jaw bone in Zol-treated rats. It is well accepted that tooth extraction is a major risk factor for the development of MRONJ ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…About 65% of these cases were cured by conservative and surgical therapies while the remaining cases did not heal. The authors have determined that the context of osteoporosis, orally administered bisphosphonates over a shorter duration of time as well as the localization of necrosis around the frontal and premolar maxilla, represent factors associated with a better outcome 53 …”
Section: Mronj Clinical Features and Classificationmentioning
confidence: 99%